Lamivudine monotherapy-based cART is efficacious for HBV treatment in HIV/HBV co-infection when baseline HBV DNA<20,000IU/ml - LI, Yijia (J Acquir Immune Defic Syndr, 2016)
BACKGROUND: Although combination antiretroviral therapy (cART) including tenofovir (TDF)+lamivudine (3TC) or emtricitabine (FTC) is recommended for treatment of HIV/HBV co-infected patients, TDF is unavailable in some resource-limited areas. Some data suggest that 3TC monotherapy-based cART may be effective in patients with low pre-treatment HBV DNA. METHODS: Prospective study of 151 Chinese HIV/HBV co-infected subjects of whom 60 received 3TC-based cART and 91 received TDF+3TC-based cART. Factors associated with HBV DNA suppression at 24 and 48 weeks, including anti-HBV drugs, baseline HBV DNA, and baseline CD4 cell count, were evaluated overall and stratified by baseline HBV DNA using Poisson regression with a robust error variance. RESULTS: Baseline HBV DNA≥20,000 IU/ml was present in 48.3% and 44.0% of subjects in the 3TC and TDF groups, respectively (P=0.60). After 48 weeks of treatment, HBV DNA suppression rates were similar between these two groups (96.8% vs. 98.0% for 3TC and TDF+3TC, P>0.999) in subjects with baseline HBV DNA<20,000 IU/ml; while in those with baseline HBV DNA ≥20,000 IU/ml, TDF+3TC was associated with higher suppression rates (34.5% vs. 72.5% in 3TC and TDF+3TC groups, respectively, P=0.002). In stratified multivariate regression, TDF use (RR 1.98, P=0.010) and baseline HBV DNA (per 1 log increase in IU/ml, RR 0.74, P<0.001) were associated with HBV DNA suppression only when baseline HBV DNA≥20,000IU/ml. CONCLUSION: This study suggests that 3TC monotherapy-based cART is efficacious for HBV treatment through 48 weeks in HIV/HBV co-infection when baseline HBV DNA<20,000IU/ml. Studies with long-term follow-up are warranted to determine if this finding persists.